Representações do corpo : com a palavra um grupo de adolescentes de classes populares - Braga, Patrícia Déa (2006)
The great importance given to the image and appearance currently is fact of public knowledge. This valuation of the body in relation to the aesthetic one was verified in previous study between adolescents of popular classrooms, which had disclosed an insatisfaction with the body, exactly being inside of the health standard. Once, with the great aesthetic concern with the corporal one demonstrated by these adolescents, the current study had as objective to know and analyse the social representations of body between adolescents of popular classrooms. One was about an inquiry of carried through qualitative boarding with a group of diligent adolescents tied with the Centro Salesiano do Menor (CESAM), situated in the city of Vitoria - ES. A random sample was selected from a list of 334 adolescents, composing a group of twenty adolescents of both sexes. Amongst these, eight girls and seven boys had been boarded by means of not-structuralized interview. The interruption of the interviews if established by means of the redundancy point, which points with respect to a repetition of the answers. From the analysis of what they said, was used the theory of the Social Representations for quarrel of the raised categories. The results had pointed that the body perception, as much for boys how much toward the girls, is come back toward the ideas of proportionality, normality and perfection. For the boys, a muscular and strong body was detached and for the girls details as hair, color of the skin and accessories of the fashion had been spoken. The desire to possess a body as in the standard propagated for the media was disclosed by the two groups. The insatisfaction with the body was stronger in the girls. The health and a functional body were remembered by the boys, associated to the question of the work. About the consequences of not having the ideal body, both had pointed situations as: exclusion, illnesses, misfortune and even death. To deepen the knowledge on the opinion, the thoughts and feelings of the relative adolescents to the body, supplies to subsidies interventions in this group, extending significantly the scope of performance in the area of the health.